Pengaruh Kualitas Pelayanan Dokter, Fasilitas Rawat Jalan, dan Pelayanan Farmasi Terhadap Kepuasan Pasien di Rumah Sakit Umum Gunung Jati Cirebon - Ade Yusuf (Tunas Medika Jurnal Kedokteran & Kesehatan, 2021)
AbstractThis research aims to determine the influences of Service Quality of Doctor, Outpatient Facilities, and Pharmacy Service, both individually or simultaneously, to Patient Satisfaction at Gunung Jati Hospital Cirebon. The research using explanatory survey method. The population of this research were all patients in the Outpatient Installation regardless of gender. Sample was taken from the population by using simple random sampling technique which amount of 100 patients. The result of the research was the Service Quality of Doctor, Outpatient Facilities and Pharmacy Service individually have positive and significant influence to Patient Satisfaction at Gunung Jati Hospital Cirebon. Service Quality of Doctor, Outpatient Facilities and Pharmacy Service simultaneouslyhave positive and significant influences to Patient Satisfaction at Gunung Jati Hospital. The total influences of those three variables are 69.8%, and the rest was influenced by other factors which not examined. Of the three variables, Service Quality of Doctor variable has the largest influence, the next is the Pharmacy Service variable, then Outpatient Facilities variable.